2011
DOI: 10.1016/j.biopsych.2010.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Habenula Volume in Bipolar Disorder and Major Depressive Disorder: A High-Resolution Magnetic Resonance Imaging Study

Abstract: Background-Increased activity of the habenula has been implicated in the etiology of major depressive disorder (MDD), in which reductions in habenula volume are present at postmortem. We conducted the first MRI analysis of habenula volume in MDD and bipolar disorder (BD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
155
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(167 citation statements)
references
References 24 publications
10
155
1
1
Order By: Relevance
“…This link with the invigoration and suppression of behavior hints at a potential role for the habenula in disorders characterized by aberrant motivated behavior, such as depression. Abnormalities in habenula structure and function have been reported in depressed patients (29,30), as well as in animal models (31). Additionally, a recent study reported that glucose metabolism in the vicinity of the habenula decreased in depressed patients following treatment with ketamine (32).…”
Section: Discussionmentioning
confidence: 99%
“…This link with the invigoration and suppression of behavior hints at a potential role for the habenula in disorders characterized by aberrant motivated behavior, such as depression. Abnormalities in habenula structure and function have been reported in depressed patients (29,30), as well as in animal models (31). Additionally, a recent study reported that glucose metabolism in the vicinity of the habenula decreased in depressed patients following treatment with ketamine (32).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, this neural network indicates that the Hb may act as a hub between forebrain and midbrain regions, together with its implication in a wide range of behaviors such as sleep-wake cycles, olfaction, ingestion, sexual behavior, stress response, reward-punishment, and pain and analgesia (Thornton et al 1985;Sugama et al 2002;Hikosaka 2010). The Hb has also been linked to various psychiatric disorders such as anxiety and depression (Savitz et al 2011a(Savitz et al , 2011b(Savitz et al , 2013, which are commonly comorbid disorders with chronic pain conditions. The role of the Hb in pain processing is well documented in animals (reviewed in Shelton et al 2012a), as well as in imaging studies of acute experimental pain in humans (Shelton et al 2012b).…”
mentioning
confidence: 94%
“…Regarding the hippocampus, some studies reported increased volume [136] as well as decreased volume [119,137]. By contrast, reports of gray matter abnormalities for dorsolateral prefrontal cortex [118,134,[138][139][140] and the habenula [141] have been infrequent but show a more consistent pattern of reduced volume. For the orbitofrontal cortex, decreased volume [117,134,142] and neuronal size reduction [143] have been reported, in addition to no alterations [144].…”
Section: Gray Matter Alterationsmentioning
confidence: 96%